The Technical Efficiency of Community Health Service Centers in Wuhan, China: Estimation and Policy Implications - Xinliang Liu MD; Quan Wang PhD; Barsanti Sara PhD; Wei Yang PhD; Siping Dong PhD; Hao Li PhD (SAGE Publishing, 2018)
This study seeks to measure the technical efficiency of Community Health Service Centers (CHSCs) in Wuhan City, China, to propose some policy recommendations to improve the efficiency of CHSCs. A total of 46 CHSCs in Wuhan City were included in the study as research subjects. Data of 11 selected input and output indicators were collected from Hubei Provincial Health and Family Planning Commission. R3.2.1 statistical software was used to estimate the efficiency scores of CHSCs using Bootstrap-Data Envelopment Analysis (DEA), and, on average, the bias-corrected technical efficiency score is found to be 0.7845. All the bias-corrected scores of CHSCs are lower than classical scores. At both local and regional level, large gaps exist in relative technical efficiency scores among the CHSCs, and 12 out of 46 CHSCs (26.09%) have efficiency scores at or below average levels. The results indicate big potential for the CHSCs in Wuhan to improve their technical efficiency, such as the optimization of health resources allocation, capacity building, information system strengthening, third party performance evaluation, and mechanisms design, and so on.